Estrategias de nutrición en el cultivo de uvilla (Physalis peruviana) y su efecto en la calidad de una bebida fermentada con el uso de dos levaduras, en la hoya de Loja. - Andrade Gordillo, Marilin Nicool (2023)
The cultivation of cape gooseberry or “uvilla” has aroused interest in recent years due to its flavor and nutritional properties, also becoming an exportable product. However, little is still known about its management and production techniques. For example, establishing efficient nutrition is essential, which is reflected in the growth and quality of the fruit, with this it is possible to transform the raw material into elaborated products, such as craft beer, giving it added value. In this sense, the best nutrition strategy in the cultivation of “uvilla” and its effect on the quality of a fermented drink compared to the use of different yeasts was determined. The test was carried out in two phases, one in the field and the other in transformation to drink. For the first phase, a completely randomized block design was applied in which three types of nutrition were tested (control without nutrition, organic nutrition and nutrition with complete inorganic fertilization) obtaining a total of 3 treatments with 8 repetitions, with 24 EU (2 plants per EU) at a distance of 2 m between rows and 1 m between plants. For the second phase, once the fruits of each field treatment were harvested, we continued to the drink fermentation stage, in which two yeast strains (S-04, K-97) were used, with 3 repetitions of the same must, with a total of 6 EU for the industrial stage. To know the effect of nutrition and strains on the quality of the beer, ANOVA type analyzes and Tukey tests at 95 % confidence were carried out, in addition, to the second stage, quantitative evaluations were carried out for the physical-chemical and qualitative characteristics in the organoleptic tests, with the help of 3 people specialized in beer tasting. Significant differences were found when applying chemical fertilization for the field stage and industrialization when applying the S04 strain. In conclusion, the best nutrition strategy that helped to enhance the quality of the “uvilla” craft beer was complete chemical nutrition based on crop requirements and soil analysis. Regarding the application of yeast strains, the S-04 strain provided us with a beer with a lower degree of acidity, pH, and STD, while when using the K-97 strain, a more acidic beer was obtained with a higher pH and STD. Regarding the organoleptic tests, the quantitative tasting results showed that when applying the S-04 yeast, the highest score of 23/30 was obtained, being a light beer, poor in foam, with a short aftertaste. Keywords: Craft beer, humic and fulvic acids, strains, organoleptic tests, aftertaste, STD.